Quantized Stabilization for T-S Fuzzy Systems With Hybrid-Triggered Mechanism and Stochastic Cyber-Attacks - Liu, Jinliang; Wei, Lili; Xie, Xiangpeng; Tian, Engang; Fei, Shumin (IEEE transactions on fuzzy systems, 2018)
This paper examines quantized stabilization for Takagi-Sugeno (T-S) fuzzy systems with a hybrid-triggered mechanism and stochastic cyber-attacks. A hybrid-triggered scheme, which is described by a Bernoulli variable, is adopted to mitigate the burden of the network. By taking the effect of the hybrid-triggered scheme and stochastic cyber-attacks into consideration, a mathematical model for a closed-loop control system with quantization is constructed. Theorems for main results are developed to guarantee the asymptotical stability of networked control systems by using Lyapunov stability theory and linear matrix inequality techniques. Based on the derived sufficient conditions in theorems, the controller gains are presented in an explicit form. Finally, two practical examples demonstrate the feasibility of designed algorithm.